Significance of m6A regulation in environmental health and safety (EHS) assessment: MWCNTs induced pulmonary toxicity through m6A modifications of mitophagy-related genes. (October 2022) - Qi, Zijuan; Huang, Xiaofeng; Feng, Wenya; Dong, Zheng; Xu, Ming; Cui, Yazhou; Xia, Tian; Liu, Sijin; Gao, Ming; Han, Jinxiang
Abstract: Multi-walled carbon nanotubes (MWCNTs) have been widely used in consumer and industrial products owing to their outstanding physicochemical characteristics. However, they have potential adverse effects on human organs, especially the lungs. Although many studies have focused on the molecular mechanisms responsible for MWCNTs-induced macrophage activation and immunotoxicity, the potential toxic effect of MWCNTs on lung cells was largely overlooked. In this study, it was found that compared with pristine (P-MWCNTs) and aminated MWCNTs (MWCNTs-NH2 ), carboxylated MWCNTs (MWCNTs-COOH) (at a dosage that failed to induce obvious cytotoxicity) can promote mitophagy occurrence and cell cycle arrest. Intriguingly, the mechanism is ascribed to an epigenetic regulation through which MWCNTs-COOH promotes the m6A modification of mitophagy-related genes by enhancing m6A methyltransferase METTL3/14 nuclear translocation, thereby leading to mitophagy-dependent cell cycle arrest in an m6A methylation-dependent manner. In addition, MWCNTs-COOH interacts with and disrupts the oligomeric structure of membrane protein caveolin-1 to activate Wnt/β-catenin pathway and then trigger m6A modification-dependent cytotoxicity. The results of this study unraveled an important role and the underlying mechanism of the surface chemical functionalization in regulating MWCNTs-induced pulmonary toxicity. This study highlights the significance of m6A regulation in assessing the environmental health and safety (EHS) impacts of MWCNTs, which can be generalized to a wide spectrum of nanomaterials. Graphical Abstract: ga1 Highlights: Sublethal dose of MWCNTs-COOH causes more toxicity than P-MWNCTs and MWCNTs-NH2 . MWCNTs-COOH specifically induces cell cycle arrest by the regulation of mitophagy. Nuclear METTL3/14 mediates the m6A modification of mitophagy-related genes. MWCNTs-COOH activates Wnt pathway to promote METTL3/14 nuclear translocation. MWCNTs-COOH binds with caveolin-1 to activate Wnt-mediated m6A modification event.